2007
DOI: 10.1038/sj.clpt.6100101
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Dextromethorphan O- and N-demethylation in the First Year of Life

Abstract: The exponential increase in the number of drugs used to treat infant and childhood illnesses necessitates an understanding of the ontogeny of drug biotransformation for the development of safe and effective therapies. Healthy infants received an oral dose (0.3 mg/kg) of dextromethorphan (DM) at 0.5, 1, 2, 4, 6, and 12 months of age. DM and its major metabolites were measured in urine. CYP2D6 genotype was determined by polymerase chain reaction-restriction fragment length polymorphism. Genotyping data indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 32 publications
9
115
2
Order By: Relevance
“…Blake et al (2) documented concordance of phenotypic O-demethylation activity and genotype (CYP2D6 activity score) from 2 wk of PNA onwards in term neonates, therefore equivalent to 42 wk PMA. The current data confirm these findings since ontogeny, i.e., age dependent maturation of O-demethylation activity mainly seems to evolve-at least in preterm neonates-until term age, equivalent to 40 wk PMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blake et al (2) documented concordance of phenotypic O-demethylation activity and genotype (CYP2D6 activity score) from 2 wk of PNA onwards in term neonates, therefore equivalent to 42 wk PMA. The current data confirm these findings since ontogeny, i.e., age dependent maturation of O-demethylation activity mainly seems to evolve-at least in preterm neonates-until term age, equivalent to 40 wk PMA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the total cytochrome (CYP) content in fetal liver is 30 to 60% of adult content, iso-enzyme specific ontogeny precludes generalization of a single developmental pattern, necessitating iso-enzyme specific assessment (1). Based on observations on in vivo dextrometorphan in healthy infants and tramadol metabolism in critically ill (pre)term neonates and young infants, phenotypic activity of N-demethylation (CYP3A) displays slower increase to adult activity compared with O-demethylation (CYP2D6) (2,3). In addition to ontogeny, co-morbidity, co-medication, or polymorphisms in drug metabolizing enzymes and transporters likely further contribute to the interindividual variability of drug disposition (1,4,5).…”
mentioning
confidence: 99%
“…It was found in one cohort that, after controlling for age, menopausal status and time since diagnosis, PMs were half as likely as EMs to report hot flushes. 90 Another cohort 107 suggested that IMs (as defined using an 'activity score' 118 ) may be more prone to hot flushes than either EMs or PMs. This cohort also found that PMs were less likely than EMs + IMs to develop severe or very severe hot flushes.…”
Section: Hot Flushesmentioning
confidence: 99%
“…Phenotypic data were obtained by High Pressure Liquid Chromatography (HPLC) according to the methods described by Abdel-Rahman et al [1] and Blake et al [3]. HPLC based phenotype was determined as follows: Six hours after the intake of 25mg dextrometorphan (DM), a prototypical CYP2D6 substrate, the concentrations of methyl-dextrorphan (MD) and its O-demethylated metabolite dextrorphan (DX)…”
Section: Cyp2d6 Phenotyping and Cyp2d6 Metabolizer Type Assignmentmentioning
confidence: 99%